What is the influence of cyclooxygenase-2 on postmenopausal endometrial polyps?. (August 2015) - Pereira, A. K. C.; Garcia, M. T.; Pinheiro, W.; Ejzenberg, D.; Soares, J. M.; Baracat, E. C.
Abstract Background The genesis of the endometrial polyp is as yet unclear. There is evidence that the polyp is related to the inflammatory process and that it interacts with the cyclooxygenase-2 (COX-2) enzyme. Objective To review the influence of COX-2 on the postmenopausal endometrial polyp. Methods A systematic review was made of the Medline, Embase, and Cochrane databases, covering the years of 2001–2014. The inclusion criteria were: experimental studies with immunohistological analysis of COX-2 in endometrial polyps; women; hysteroscopic and surgical evaluation; and studies with comparisons between the endometrial polyp and other tissues (normal endometrium, adjacent endometrium, and other uterine diseases). The exclusion criteria were: polyps in other organs; genetic polymorphisms; endometrial cancer exclusively; abnormal uterine bleeding unrelated to polyps. The search key words (taken from the Medical Subject Headings – MeSH) were endometrial polyp and cyclooxygenase-2. Results Seven of ten articles were selected. Results showed positive COX-2 expression in the glandular epithelium of the polyps, and expression was more intense when the polyp was malignant. However, there was a study which did not find any difference between polyps and the normal endometrium, and there was another which compared polyps in menacme with postmenopausal polyps. Conclusion There is no consensus in the literature as to the participation of COX-2 in the development of benign and/or malignant endometrial polyps. In all of the studies, COX-2 was present in the postmenopausal polyps and with greater intensity in the malignant ones.